2017
DOI: 10.2217/cer-2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of APT198K for the treatment of infantile colic: a pilot study

Abstract: APT198K decreased the mean duration per crying episode significantly more than a lactase dietary supplement in infants with colic. Further evaluation in larger studies is warranted. Clinical trial registry: EudraCT number 2014-002860-334; https://eudract.ema.europa.eu .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…In a pilot study in 46 infants aged 3--16 weeks with infantile colic, the administration of xyloglucan plus heat-killed Lactobacillus reuteri SGL01 and Bifidobacterium brevis SGB01 significantly decreased the mean duration of crying episodes, in comparison with a lactase dietary supplement. These results suggest a role of xyloglucan in the management of infantile coli, although further research in larger studies is needed [ 76 ].…”
Section: Clinical Studies With Xyloglucan In Infantile Colicmentioning
confidence: 99%
“…In a pilot study in 46 infants aged 3--16 weeks with infantile colic, the administration of xyloglucan plus heat-killed Lactobacillus reuteri SGL01 and Bifidobacterium brevis SGB01 significantly decreased the mean duration of crying episodes, in comparison with a lactase dietary supplement. These results suggest a role of xyloglucan in the management of infantile coli, although further research in larger studies is needed [ 76 ].…”
Section: Clinical Studies With Xyloglucan In Infantile Colicmentioning
confidence: 99%
“…The resting periods between heating periods allow surviving spores to develop into bacterial cells, which will then be destroyed by the next day’s heating. Tyndallized probiotics L. reuteri SGL01 100 × 10 9 colony-forming units (CFU)/g and B. breve SGB01 100 × 10 9 CFU/g were recently compared to lactase in a clinical trial 53 . Both interventions reduced crying time, which may be related to the placebo effect or to the fact that both interventions are indeed effective, but APT198K decreased the mean duration per crying episode significantly more than a lactase dietary supplement in infants with colic 53 .…”
Section: Managementmentioning
confidence: 99%
“…Tyndallized probiotics L. reuteri SGL01 100 × 10 9 colony-forming units (CFU)/g and B. breve SGB01 100 × 10 9 CFU/g were recently compared to lactase in a clinical trial 53 . Both interventions reduced crying time, which may be related to the placebo effect or to the fact that both interventions are indeed effective, but APT198K decreased the mean duration per crying episode significantly more than a lactase dietary supplement in infants with colic 53 . A trial comparing a combination of Matricaria chamomilla , Melissa officinalis , and tyndallized L. acidophilus (HA122) with L. reuteri DSM 17938 and with simethicone showed that simethicone was not effective but both other arms were equally effective 29 .…”
Section: Managementmentioning
confidence: 99%
“…In experimental animal models [ 20 ] and in human clinical trials [ 21 , 22 ], positive effects of heat-killed bacteria in different conditions have been observed, such as probiotic administration in neonates, without the risks associated with live bacteria [ 23 , 24 ]. Preparations with dead or live microorganisms and metabolites have shown good biological properties in terms of reestablishing intestinal homeostasis; in many cases, these effects are similar to those obtained with the administration of live bacteria [ 20 , 25 ].…”
Section: Introductionmentioning
confidence: 99%